EFFECT LEADERSHIP STYLE AND SUPERVISION ON PERFORMANCE KERINCI POLICE OFFICERS WITH WORK CLIMATE AS THE INTERVENING VARIABLE - Mera, Yandra; Ali, Helmi (STIE Bangkinang Publishing, 2022)
This study aims to determine and analyze the influence of leadership style and supervision on work climate, influence of leadership style and influence of supervision on employee performance, influence of work climate and influence of leadership style on performance with work climate as intervening variable and the effect of supervision on performance with work climate as the intervening variable. The sample in this study were Kerinci Police officers totaling 217 people. The sampling technique is a census technique because the number of employees is only 217 people who fill out the questionnaire. The type of data used is primary data, the data collection method uses a questionnaire with a Likert scale. Test the research instrument validity and reliability test. Data analysis techniques consist of data description test, classical assumption test, path analysis and hypothesis testing. The results of the study found that leadership style had a positive and significant effect on employee work climate, supervision had a positive and significant effect on employee work climate, leadership style had a positive and significant effect on employee performance, supervision had a positive and significant effect on employee performance, work climate had a positive and significant effect on employee performance. on employee performance, work climate does not act as an intervening variable between leadership style and employee performance and work climate does not act as an intervening variable between supervision and employee performance.